A comparison of barriers to mental health support‐seeking among farming and non‐farming adults in rural South Australia. (15th June 2017) - Hull, Melissa J.; Fennell, Kate M.; Vallury, Kari; Jones, Martin; Dollman, James
Abstract: Objective: To assess the differences between farming and non‐farming rural adults in perceived barriers to mental health service use. Design: A cross‐sectional survey, modified from the Barriers to Help‐Seeking Scale (BHSS), was conducted using a computer‐assisted telephone interview. Setting: Respondents (age 52.6 ± 11.6 years) were recruited from three rural regions of South Australia. Participants: Approximately, 78 non‐farmers and 45 farmers were included in analyses. 78 retired and two unemployed participants were excluded from the analyses. Main outcome measure: Farmers and non‐farmers were compared on domain scores and individual item responses from the adapted BHSS that represent 'agrarian' attitudes to support‐seeking for mental health: stoicism, self‐reliance, minimisation of the problem, stigma and distrust of health professionals. Results: In the analysis of domain scores, 'Need for Control and Self‐Reliance' was a stronger barrier for farmers than non‐farmers ( P = 0.009) with a trend ( P = 0.07) towards stronger barriers among farmers in the 'Minimising Problem and Resignation' domain. In the analysis of item‐level responses, there was a difference ( P = 0.03) between farmers and non‐farmers in responses to 'I find it difficult to understand my doctor/health professional', with 24.4% of the farmers agreeing that this is a barrier compared with 15.3% of the non‐farmers. Conclusion: Long‐held stereotypes of stoicism and self‐reliance among farmers were somewhat supported, in the context of mental health. Mental health services and professionals in rural Australia might need to adapt their practices to successfully engage this population.